Profiling leucocyte subsets in tuberculosis–diabetes co-morbidity - Kumar, Nathella Pavan (Immunology, 2015)
The immune system plays an important role in the pathogenesis of pulmonary tuberculosis–type 2 diabetes mellitus (PTB-DM) co-morbidity. However, the phenotypic profile of leucocyte subsets at homeostasis in individuals with active or latent tuberculosis (LTB) with coincident diabetes is not known. To characterize the influence of diabetes on leucocyte phenotypes in PTB or LTB, we examined the frequency (F(o)) of leucocyte subsets in individuals with TB with (PTB-DM) or without (PTB) diabetes; individuals with latent TB with (LTB-DM) or without (LTB) diabetes and non-TB-infected individuals with (NTB-DM) or without (NTB) diabetes. Coincident DM is characterized by significantly lower F(o) of effector memory CD4(+) T cells in LTB individuals. In contrast, DM is characterized by significantly lower F(o) of effector memory CD8(+) T cells and significantly higher F(o) of central memory CD8(+) T cells in PTB individuals. Coincident DM resulted in significantly higher F(o) of classical memory B cells in PTB and significantly higher F(o) of activated memory and atypical B cells in LTB individuals. Coincident DM resulted in significantly lower F(o) of classical and intermediate monocytes in PTB, LTB and NTB individuals. Finally, DM resulted in significantly lower F(o) of myeloid and plasmacytoid dendritic cells in PTB, LTB and NTB individuals. Our data reveal that coincident diabetes alters the cellular subset distribution of T cells, B cells, dendritic cells and monocytes in both individuals with active TB and those with latent TB, thus potentially impacting the pathogenesis of this co-morbid condition.